2013
DOI: 10.4103/0378-6323.110767
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic evaluation of therapeutic response to an intralesional corticosteroid in the treatment of alopecia areata

Abstract: Intralesional triamcinolone acetonide is efficacious for treatment of localized patchy alopecia areata. Dermoscopy is very useful to identify signs of early clinical response, adverse effects and markers of disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 0 publications
2
20
1
Order By: Relevance
“…Thappa et al preferred tincture iodine and anthralin as first line. [65] Long-term use of systemic steroids is generally not recommended because of potential side effects. Psychological effects are of major concern in children, and they should be attended to with proper counseling.…”
Section: Miscellaneous Miscellaneousmentioning
confidence: 99%
See 4 more Smart Citations
“…Thappa et al preferred tincture iodine and anthralin as first line. [65] Long-term use of systemic steroids is generally not recommended because of potential side effects. Psychological effects are of major concern in children, and they should be attended to with proper counseling.…”
Section: Miscellaneous Miscellaneousmentioning
confidence: 99%
“…[109] Tincture iodine has been suggested as a non-specific irritant in patchy AA patients with less than 10 years of age. [65] Topical bexarotene 1% gel was evaluated in single-blinded half head study and found 50% or more partial regrowth in 12% of patients on the treated side and in 14% responded on both sides. [95] Fractional Er: Glass laser has shown complete hair regrowth in a single patient who was not responding to conventional therapies.…”
Section: Miscellaneous Miscellaneousmentioning
confidence: 99%
See 3 more Smart Citations